Archaeology of the Night : Life After Dark in the Ancient World - Nowell, April, 1969-; Gonlin, Nancy (Book collections on Project MUSE., 2018)
"A diverse team of experienced scholars used a variety of methods and resources to reconstruct how ancient peoples experienced the night, their views of the dark, their portrayals of the night, and how people in everyday life adapted to the night "--Provided by publisher